HYBRID ESP-NOW AND MQTT-BASED MONITORING AND EARLY WARNING SYSTEM FOR RRI MANADO TRANSMITTER ROOM - Evert Paul Mangimbelat; Melyssa Christy Pasiowan; Febrita Bungkaes; Maksy Sendiang; Anthoinete Pemina Yece Waroh (Jurnal Riset Informatika, 2026)
The transmitter room of LPP RRI Manado is a vital operational center housing high-power electronic equipment susceptible to damage from temperature fluctuations, humidity instability, abnormal machine noise, and fire hazards. Currently, no automated monitoring system has been implemented to continuously observe environmental conditions in real-time, resulting in delayed detection of technical anomalies. This research aims to design and implement an IoT-based monitoring and early warning system for the transmitter room environment. The novelty of this system lies in its hybrid ESP-NOW and MQTT communication architecture, specifically tailored for the multi-parameter environmental monitoring demands of broadcast transmitter facilities, where neither protocol alone could fulfill both low-latency local transmission and real-time remote dashboard access simultaneously. The system employs ESP-NOW for wireless inter-building data transmission and MQTT for real-time integration to a web-based monitoring dashboard. Environmental parameters were selected based on the primary physical risk factors in high-power electronic environments: temperature and humidity (DHT22) to detect thermal and moisture anomalies, sound intensity (GY-MAX4466) to identify mechanical failure indicators, and smoke concentration (MQ-2) as an early fire hazard indicator. The research method used is quantitative with an experimental approach, whereby numerical data were collected from sensor readings and communication performance tests, then analyzed to evaluate system accuracy, latency, and packet loss. The expected outcome is a system that enables centralized monitoring for TMB technicians and delivers early warning notifications when abnormal conditions are detected, ensuring operational reliability and continuity of LPP RRI Manado broadcast services.